‘TAQUARI’, A new and a promising mango material: Emergence, post-harvest and biometrics of fruit - Nacata, Guilherme; de ANDRADE, Renata Aparecida [UNESP]; Marques, Kelly Magalhães; Marino, Ariadne Kaleda [UNESP]; Mattiuz, Ben-Hur [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2018)
The fruit of ‘Taquari’ have attractive appearance, with intense yellow flesh, pleasant taste and absence of fibers, which makes it a potential material for, after a series of studies, being released as a variety. For biometrics, 50 mature fruit were used the results (average of three samples) were evaluated by descriptive statistics using central trend (average) and variability of data (standard error and coefficient of variation). For the germination test, the seeds were extracted from ripe fruit and dried; subsequently, they were germinated in sachets containing the mixture soil:sand:corral manure (3:1:1) as substrate, evaluating seedling emergence and polyembryony. The design was in randomized blocks and 5 treatments were studied, with 5 replicates each and 10 seeds per replicate. The percentage data were transformed into arc-sen, submitted to analysis of variance and the means, to Tukey test at 5% probability. For fruit quality characterization, 12 ripe fruits were used, separated into 3 lots with 4 fruit, using a completely randomized design. The fruit were characterized regarding firmness, peel and pulp color, soluble solids, titratable acidity, pH, ascorbic acid and respiratory rate. We conclude that the ‘Taquari’ has fruit with interesting characteristics for the Brazilian market and there is a better seedling emergence in the absence of seed coat, but with a greater occurrence of polyembryony. For quality characterization, the fruit present parameters such as soluble solids and titratable acidity similar to the main varieties of mangoes sold in the country, but with emphasis to the high ascorbic acid content detected.
‘Taquari’: Um novo e promissor material de mangueira
Keywords: Chemical characterization; Mangifera indica L.; Polyembryony; Propagation